A qualitative exploration of students’ perceptions, graph description skill development, and challenges in using the Knight of Kingdom Language Boardgame (KOKLAB) - Abdul Rahman, Ayuni Madarina (Journal of Islamic, Social, Economics and Development, 2026)
Boardgame-based learning has garnered attention in language education due to its ability to motivate students and promote meaningful communication. The objective of this study is to examine students’ perceptions of the boardgame in learning to describe graphs and charts, investigate its impact on confidence and emotional responses, and identify challenges encountered by students. This study employed a qualitative design to explore students’ experiences in using the Knight of Kingdom Language Boardgame (KOKLAB) as a complementary learning tool in a tertiary-level communicative English classroom. Five students were selected as participants as they had experienced using KOKLAB. Semi-structured interviews were conducted to gain in-depth perspectives. The interview transcripts were analysed thematically to identify recurring themes. The findings indicate that students generally perceived KOKLAB as familiar and accessible due to its interactive element, which supported active engagement. Students reported having opportunities to practice the language forms and functions of describing graphs and charts during the gameplay. Several impacts were identified including improved confidence, and positive emotional engagement although some experienced pressure related to time constraints and the competitive elements. The findings suggest that the use of boardgame can contribute to an effective learning environment with careful consideration of task design and pacing.